The waning of the green catholics, the Irish, and identity in Toronto, 1887-1922 - McGowan, Mark, 1959- (Montreal : McGill-Queen's University Press, 1999)
"Most historical accounts of the Irish Catholic community in Toronto describe it as a poor underclass of society, ghettoized by the largely British, Protestant population and characterized by the sectarian violence between Protestants and Catholics that earned Toronto the title "Belfast of Canada." Challenging this long-standing view of the Irish Catholic experience, Mark McGowan provides a new picture of the community's evolution and integration into Canadian society." "McGowan's detailed and lively portrait will be of great interest to students and scholars of religious history, Irish studies, ethnic history, and Canadian history."--BOOK JACKET.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Catholics -- Ontario -- Toronto -- History; Irish Canadians -- Ontario -- Toronto -- History; Catholiques -- Ontario -- Toronto -- Histoire; Canadiens d'origine irlandaise -- Ontario -- Toronto -- Histoire; Ieren; Rooms-katholieken.; Etnisch bewustzijn; Assimilatie (sociologie); Acculturatie; HISTORY / Canada / General; Electronic books